Two new species of the genus Rhyacophila Pictet (Trichoptera, Rhyacophilidae) from Korea and Japan - Nozaki, Takao; Park, Sun-Jin (Zootaxa, 2021)
Two new species of the genus Rhyacophila Pictet, R. kangae Park & Nozaki sp. nov. and R. yamamotoi Nozaki sp. nov., are described from Korea and Japan, respectively. Both species belong to the Rhyacophila nigrocephala Species Group, and their genitalic morphology is very similar to those of R. confissa Botosaneanu 1970 and R. vicina Botosaneanu 1970 described from the Korean Peninsula. These four species can be distinguished from each other by the shape of the complex of preanal appendages and apicodorsal lobe of segment IX in males, and by the shape of the vaginal apparatus in females. Males of the two new species bear larger compound eyes in proportion to the head widths than those of R. confissa and R. vicina.